Identifying Opportunities to Improve Guideline-Concordant Antibiotic Prescribing in Veterans with Acute Respiratory Infections or Cystitis. (11th April 2017) - Meyer, Hayley E.; Lund, Brian C.; Heintz, Brett H.; Alexander, Bruce; Egge, Jason A.; Livorsi, Daniel J.
Abstract : We investigated the frequency and determinants of guideline-discordant antibiotic prescribing in outpatients with respiratory infections or cystitis. Antibiotic prescribing was guideline discordant in 60% of patients. The most common reason for discordance was prescribing an antibiotic when not indicated. In a multivariate analysis, physicians in training had the highest likelihood of guideline-concordant antibiotic prescribing. Infect Control Hosp Epidemiol 2017;38:724–728